Vagal Nerve Stimulation in the Pediatric Population and Correlation between Family and Treatment Team Perspectives: Single-Center Experience - Alnaami, Ibrahim; Algarni, Abdullah; Alqahtani, Saeed A.; Alqahtani, Rawan M.; Jabbar, Imtinan Al; Alhadi, Wajd; Alnujaymi, Bayan M.; Alahmari, Seham A.; Asiri, Dina; AlQahtani, Asma M.; Otaif, Mansour Y. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Background Vagal nerve stimulation (VNS) is an adjunctive therapy to pharmacologic treatment in patients with drug-resistant epilepsy. This study aimed to assess the efficacy of VNS therapy for seizure frequency reduction and improving the quality-of-life (QOL) measures in children with refractory epilepsy and to evaluate the correlation between the perspectives of families and those of the treating team.Methods This was a prospective cohort study conducted at Abha Maternity and Children's Hospital, Saudi Arabia, from 2018 to 2022. A total of 21 pediatric patients who completed 1 year of follow-up after VNS implantation were included. Patients were aged between 2 and 14 years, with a mean age of 8.14 ± 3.92 years; 11 (52.4%) patients were females. Family and physician assessments were collected blinded to each other using the Clinical Global Impression of Improvement (CGI-I) scores and QOL assessments to evaluate the correlation between the families' and treating team's perspectives on VNS outcomes.Results In this study, VNS showed significant efficacy in reducing the frequency of seizures. VNS significantly reduced the number of seizures per week from a baseline median of 35 to a median of 0.25 at the end of the follow-up period, representing a dramatic reduction of 99.3% (p < 0.001). The number of emergency department visits per year decreased from a baseline median of 12 to a median of 2, a reduction of 83.3% (p < 0.001), while the number of hospital admissions per year decreased from a baseline median of 3 to a median of 1, a 66.7% decrease (p < 0.001). The number of antiepileptic medications taken decreased from a median of four to three (p < 0.001). Notably, 28.57% of the patients achieved complete seizure freedom, and 38% exhibited significant improvement, with at least 50% reduction in seizure frequency. Importantly, none of the patients experienced an increase in seizure frequency following VNS treatment. The family and physician assessments showed varying degrees of alignment in perceptions, with “concentration” exhibiting a significant positive correlation (r = 0.498, p = 0.022), indicating noteworthy agreement, whereas verbal communication did not show a substantial correlation (r = − 0.062, p = 0.791), indicating a divergence of views.Conclusion VNS is a promising and well-tolerated therapy for individuals with intractable seizures, offering clinical benefits and potential enhancements in various aspects of QOL. The varying perceptions between family and physician assessments highlight the importance of considering multiple perspectives when evaluating treatment outcomes.
Keywords: VNS; seizure; epilepsy; family perspective; QOL